2002
DOI: 10.1177/019263650208663002
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Among 9th Graders: An Exploratory Study

Abstract: This study describes the bullying behaviors reported by 136 grade 9 students in two high schools in the same Southern city. Nearly 75% of students reported observing some type of bullying at their school. Bullied students were most apt to tell their mother or a friend about their experience, but rarely told a teacher or an administrator. Findings also suggest that the students surveyed did not perceive their teachers or administrators to be interested in reducing bullying. Recommendations to help school admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
1
14
1
3
Order By: Relevance
“…The nature and pattern of this bullying was generally in line with the findings of other studies of bullying in primary schools (Harris, Petrie, & Willoughby, 2002;Mellor, 1999;Wolke et al, 2001;Smith & Shu, 2000). Bullying usually took place outside the school buildings, in the school grounds.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The nature and pattern of this bullying was generally in line with the findings of other studies of bullying in primary schools (Harris, Petrie, & Willoughby, 2002;Mellor, 1999;Wolke et al, 2001;Smith & Shu, 2000). Bullying usually took place outside the school buildings, in the school grounds.…”
Section: Resultssupporting
confidence: 88%
“…There are fewer studies which have examined pupils' views about their teachers' attitudes to issues of behaviour. Harris, Petrie, and Willoughby (2002) reported evidence from American Grade 9 schoolchildren that a large proportion of them believed that their teachers were not interested in reducing bullying. Similarly, Boulton and Underwood (1993) and Whitney and Smith (1993) in studies of English schoolchildren found that the proportion of students who believed that their teachers almost always attempted to put an end to bullying was small.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of age, research suggests that the number of victims is highest at the elementary level, increasing with the age of the children until the beginning of secondary school, at which point the level of victimization tend to decrease (Harries et al 2002). In general, victims are described as younger, shorter, and weaker than their peers (Hazler et al 1997;Olweus 1997), with a style of dress that deviates from the norm (Ma 2001).…”
Section: Conceptualization Of the Phenomenonmentioning
confidence: 99%
“…Selon plusieurs auteurs, lorsqu'un enfant intimide les autres, il est susceptible de souffrir de problèmes psychologiques incluant les troubles de conduite, une tendance à l'agressivité et des symptômes occasionnels de dépression (Artz et Nicholson, 2002 ;Harris, Petrie et Willoughby, 2002). Ces comportements d'intimidation peuvent persister tout au long de la vie en l'absence d'intervention appropriée (Rigby, Smith et Pepler, 2004).…”
Section: Concept D'intimidationunclassified